Experiences and outcomes of Gypsy, Roma and Traveller women in pregnancy: a scoping review protocol - Mary Higgins; Maggie O’Brien; Brendan Dempsey (BMJ Open)
Introduction Gypsy, Roma and Traveller communities are subjected to a specific form of racism fuelled by deep-seated prejudice and stereotypes. These groups have historically been the victims of school segregation, forced assimilation policies, hate speech and hate crimes.Persecution and displacement have resulted in high rates of unemployment, reduced access to education and poorer health in general, which places these groups at significantly increased risk of poverty. In pregnancy, they are at increased risk of adverse obstetric outcomes. There is a gap in the literature surrounding the experiences and outcomes of pregnant women within this group. A scoping review was chosen as the appropriate methodology to identify what is known about the experiences and outcomes of pregnant women in these communities.Methods and Analysis The Levac et al guideline on conducting a scoping review will be followed. This six-step approach includes identification of the research question, identification of relevant studies, selection of studies, charting of data, summary of results and consultation with experiential experts. A comprehensive search of the following electronic databases from 1980 to 2021 will be conducted: CINAHL, Embase, MEDLINE, Scopus and Web of Science. Relevant grey literature and reference lists will also be searched. The Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) tool will be used.Ethics and dissemination Ethical approval was not required for this protocol as all literature within this scoping review are publicly available. To facilitate dissemination of findings, the research team will present the findings to key stakeholders working with Gypsy, Roma and Traveller communities.